Caring for children with an intellectual disability: An exploratory qualitative study. Issue 2 (4th March 2019) - Sadiki, Tshimangadzo Getrude; Mashegoane, Solomon
Abstract : This study explored family caregiver experiences of children with an intellectual disability in a rural South African day-care centre. The family caregivers ( N = 15; mothers = 60%; age range = 35 to 68 years) completed in-depth interviews regarding their experiences providing care to children with intellectual disability. Data collection and analysis was done using phenomenological methods. The following themes emerged to characterise the family caregiver experiences: deeper understanding of intellectual disability; disability disclosure conditions; and social and economic support needs. Family support emerged as an important factor in the relationship between caregivers' psychological stress and well-being.